MAKNA SIMBOLIK DAN WUJUD ESTETIK NAGA DALAM KEBUDAYAAN JAWA - Ceptian Suryana (Universitas Komputer Indonesia, 2018)
This study examines the symbolic meaning and the aesthetic form of the dragon contained in the visual form of the stretch of the Dwi Naga Rasa Tunggal and Dwi Naga Rasa Wani. The method used in this research is descriptive qualitative. The symbolic meaning is examined through the basic patterns of Javanese society that influence Javanese society in constructing artifacts. After that, the aesthetic form is analyzed through indicators of color, shape, size and proportion. Based on the analysis, the shapes of the dragons on the three parts have the same meaning to each other, namely the representation of the Javanese way of thinking, as a 'rice field' society. From the basic pattern seen in the ornamental ornament as well as the shape and position of the dragon on the ladder, the Javanese community's relationship with his Lord can be found, in the form of hopes for fertility in agriculture, safety, and blessing in life. When viewed from its overall shape, the shape of the dragon in these three parts also has similarities in the shape of the headdress, head shape and body shape.